Does loan growth impact on bank risk? - Shih-Wei Wu; Manh-Thao Nguyen; Phi-Hung Nguyen (Heliyon, 2022)
In the context of competition between domestic banks but also foreign banks become more and more fierce. The increasing penetration of foreign banks brings certain risks to domestic banks. This study was conducted to assess the effect of loan growth on banking risk in Vietnam. The study collects data on 29 banks listed on the Vietnam stock exchange from 2010 to 2020. The results of panel data analysis with Generalized least squares (GLS) have shown a relationship between loan growth and bank risk. In which loan growth has a negative impact on Non-performing loans (NPL), liquidity risk equity on asset (ETA); loan growth has a positive impact on return (ROA). In addition, the study also conducts a comparative assessment by bank size and loan growth rate. The results indicate a difference in loan growth's impact on banks' bank risk with lower and higher assets and lower and higher loan growth rates. From the results of this study, the authors also provide some implications to help banks reduce bank risk based on loan growth strategy.